ANALYSIS OF KIKY SAPUTRI’S ROASTING AS CRITIQUES TOWARDS POLITICIANS - Lambok Hermanto Sihombing; Farda Mufidah Adzra; Rahmatia Rahadi (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2021)
Recently, roasting as one of the stand-up comedy techniques has become an entertainment favored by Indonesian people. Roasting is a series of jokes that aims to comment on a specific person. This study will use data from one of the videos on YouTube showing Kiky Saputri roasting four ministers, namely Hanif Dhakari, Rudiantara, Retno Marsudi, and Susi Pudjiastuti. This study will use the theory of humor and satire to find out the meaning of Kiky's roasting material. This study shows that each roasting word given by Kiky has a meaning and is interrelated between humorous and satirical sentences.